Rhodospirillum centenum Utilizes Separate Motor and Switch Components To Control Lateral and Polar Flagellum Rotation - McClain, Jonathan (American Society for Microbiology, 2002)
Rhodospirillum centenum is a purple photosynthetic bacterium that is capable of differentiating from vibrioid swimming cells that contain a single polar flagellum into rod-shaped swarming cells that have a polar flagellum plus numerous lateral flagella. Microscopic studies have demonstrated that the polar flagellum is constitutively present and that the lateral flagella are found only when the cells are grown on solidified or viscous medium. In this study, we demonstrated that R. centenum contains two sets of motor and switch genes, one set for the lateral flagella and the other for the polar flagellum. Electron microscopic analysis indicated that polar and lateral flagellum-specific FliG, FliM, and FliN switch proteins are necessary for assembly of the respective flagella. In contrast, separate polar and lateral MotA and MotB motor subunits are shown to be required for motility but are not needed for the synthesis of polar and lateral flagella. Phylogenetic analysis indicates that the polar and lateral FliG, FliM, and FliN switch proteins are closely related and most likely arose as a gene duplication event. However, phylogenetic analysis of the MotA and MotB motor subunits suggests that the polar flagellum may have obtained a set of motor genes through a lateral transfer event.